The Effect of Career Exploration Behavior and Parent-Child Career Congruence on College Student Career Adaptability - Putri, Shafira Oktaviani; Salim, Rose Mini Agoes (Jurnal Kajian Bimbingan dan Konseling, 2021)
Career adaptability can help college students to face the tasks that will arise in the world of work. This study aims to examine the effect of career exploration behavior and parent-child career congruence on career adaptability simultaneously and to see which variables contribute more to career adaptability. The participants involved in this study were final semester college students, starting from sixth semester in four Indonesian cities, namely Jakarta, Bogor, Tangerang, Bekasi, with a total of 538 students. This study used a non-experimental cross-sectional research design because data was only taken once, and non-probability convenience sampling was used. The measuring instruments used are Career Adapt-Abilities Scale, Career Exploration Behavior, and The Adolescent-Parent Career Congruence. The data obtained were then analyzed using a multiple regression test. The results showed that there was a simultaneous significant effect of career exploration behavior and parent-child career congruence on career adaptability. The results also show that career exploration behavior contributes more to career adaptability than parent-child career congruence. The research results can be used for college students to improve the ability of career adaptability through exploration and congruence activities.